The impact of smallholder cocoa production on rural livelihoods : case study in the Solomon Islands : a thesis presented in partial fulfilment of the requirements for the degree of Master of AgriScience at Massey University, Palmerston North, New Zealand - Hivu, Dorcas Oroi (Massey University, 2013)
Through its working policy, the Solomon Islands government aimed to increase smallholder production of cash crop products, such as cocoa, through which the country not only earned revenue but farmers also earned income. As such, smallholder farmers in the Solomon Islands have been encouraged to venture into cash crop earning activities. In the last decades, donor agencies have been involved a lot with farmers to increase cash crop production. However, rural households depend largely on subsistence activities for their livelihood. Based on the understanding that a lot of assistance has been given to smallholder farmers throughout the country, both by the government and outside aid agencies, this study seeks to investigate the impact of smallholder cash crop production on rural livelihoods. A qualitative case study approach was utilised in this study. Data was collected through semi-structured interviews with farmers. This study used the Sustainable Livelihood Framework as a guide to investigate the livelihoods at household level. The results show that household’s involvement in cash crop production is facilitated by the church with very limited support from the central government. This study provides an empirical example of how a community integrates cash cropping as part of their livelihood through their own initiatives. Factors which enable households to integrate cash crops as a part of their livelihood include: motivation to participate due to community commitment to the church; access to a trusted market; nature of the crop; and labour availability. Cash cropping, as shown in this study, does not undermine or substitute food production since there is abundant land available. Results also show that cash cropping has significantly improved household income and consequently increase household standard of living. This research found that the benefits of cash cropping are distributed across all households within the community as all households grow crops. Households benefit directly from cash cropping through access to cash. Access to cash opens up opportunities for households and/or individuals to venture into other livelihood activities within the community. This study also found that cash cropping has some negative implications. Access to cash through cash cropping results in a change in cultural expectations towards cash; a change in children’s attitude towards education; decreased participation in communal work; and contributes to reduction in the cultivation of traditional crops with cultural importance to the community. This research suggests that institutions through which rural households have access to and/or benefit from cash cropping should be supported by the government.
Keywords: Cacao growers; Cacao; Cocoa farming; Agriculture; Economic aspects; Solomon Islands; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Horticulture